INTEGRATING ISLAMIC FINANCIAL LITERACY INTO AL-ISLAM AND KEMUHAMMADIYAHAN CURRICULUM: A STUDY AT MUHAMMADIYAH UNIVERSITY OF SIDOARJO - Faizah, Ima; Faridi, Faridi; Tobroni, Tobroni (Journal of Learning on History and Social Sciences, 2025)
Objective: This study investigates the level of Islamic financial literacy and lifestyle among students at Muhammadiyah University of Sidoarjo, alongside analyzing the integration of Islamic financial literacy within Islamic Religious Education courses. Method: Utilizing a mixed-methods approach combining descriptive quantitative surveys and qualitative content analysis, this research seeks to capture both statistical trends and curriculum-based insights. Results: The research reveals that while students exhibit moderate to good Islamic financial literacy and lifestyle, gaps remain in their understanding of contemporary financial transactions, indicating a need for deeper instructional focus. Novelty: This study contributes to the theoretical discourse on Islamic financial education and offers practical insights for educators to align religious instruction—particularly in the Ibadah Akhlak Muamalah course—with the evolving financial landscape, ensuring that the principles of halal and haram are considered in modern economic practices.